1995
DOI: 10.1530/eje.0.1330294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid dysfunction in different geriatric subpopulations from a moderately iodine-deficient Hungarian region. Comparative clinical and hormonal screening

Abstract: The aim of this study was to investigate the prevalence of thyroid dysfunction in different geriatric subpopulations from a moderately iodine-deficient Hungarian region and to compare the efficacy of clinical versus hormonal screening. A screening study was done on 279 chronically ill geriatric patients (Group I) and 256 consecutive hospital admissions over 60 years of age (Group II). The method of clinical screening was different from those used so far: the object was not to search for symptoms of hypo- or hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In old age, especially in iodine-depleted geographical areas, there is an increased prevalence of goitre and thyroid nodules, and hyperthyroidism of non-autoimmune origin seems to be more frequent (Herrmann, 1981;Hegedüs et al, 1983;Olbricht et al, 1983;Oberhofer et al, 1989;Szabolcs et al, 1990Szabolcs et al, , 1995bHintze et al, 1991;Gönczi et al, 1994). On the other hand, in regions with good iodine supply hypothyroidism occurs more frequently (Sawin et al, 1985;Robuschi et al, 1987;Rosenthal et al, 1987;Brochmann et al, 1988;Okamura et al, 1989;Parle et al, 1991;Sundbeck et al, 1991).…”
mentioning
confidence: 99%
“…In old age, especially in iodine-depleted geographical areas, there is an increased prevalence of goitre and thyroid nodules, and hyperthyroidism of non-autoimmune origin seems to be more frequent (Herrmann, 1981;Hegedüs et al, 1983;Olbricht et al, 1983;Oberhofer et al, 1989;Szabolcs et al, 1990Szabolcs et al, , 1995bHintze et al, 1991;Gönczi et al, 1994). On the other hand, in regions with good iodine supply hypothyroidism occurs more frequently (Sawin et al, 1985;Robuschi et al, 1987;Rosenthal et al, 1987;Brochmann et al, 1988;Okamura et al, 1989;Parle et al, 1991;Sundbeck et al, 1991).…”
mentioning
confidence: 99%
“…In previous studies we reported on the high prevalence of clinical and subclinical thyroid dysfunctions in chronically ill hospitalized geriatric patients living in moderately iodine deficient areas (14.4% in Germany or 13.3% in Hungary) (Szabolcs et al, 1990(Szabolcs et al, , 1995(Szabolcs et al, , 1997. Besides of this high prevalence, there are other good reasons to recommend thyroid screening of this elderly subpopulation as well:…”
Section: Introductionmentioning
confidence: 99%
“…When should chronically ill hospitalized geriatric patients be screened for thyroid dysfunctions? The general view is that thyroid screening is not indicated upon acute hospital admission because nonthyroidal illnesses may influence the thyroid parameters (Small et al, 1990;Szabolcs et al, 1995). Chronically ill geriatric patient do have nonthyroidal illnesses but these are ªper seº non-acute disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, such as Hungary, a well-estab¬ lished network of blood spot TSH screening for congenital has been recognized that the clinical detection of thyhypothyroidism exists, which could be used for screening in roid dysfunction in the elderly is difficult to distinguish the elderly as well, from the signs and symptoms of aging (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Thus, there is In two previous studies, the efficiency of the blood spot good reason to recommend biochemical screening of the elversus sensitive serum TSH screening was investigated in el¬ derly, at least in areas of abundant iodine intake, where the derly subjects.…”
mentioning
confidence: 99%